Let's talk about Down syndrome - Gordon, Melanie Apel. (New York : Rosen/PowerKids Press, 1998)
Summary : Describes what causes Down syndrome and how it affects those children who have it, stressing how they can be helped to lead happy lives.
Describes what causes Down syndrome and how it affects those children who have it, stressing how they can be helped to lead happy lives.
Includes index.
880
Accelerated Reader AR
Keywords: Down syndrome; People with mental disabilities